Intervensi Dini Bersumberdaya Keluarga: Meningkatkan Keterampilan Orangtua Melalui Program Parenting bagi Anak Berkebutuhan Khusus - Shinta Malida Balqis; Sunardi Sunardi; Endang Rochyadi (Jurnal Penelitian Pendidikan Khusus, 2022)
The purpose of this study is reviewing programs that have been made by previous researchers and then analyzed through a theoretical approach. The method used in this study is a systematic review of existing literature reviews. 3 (three) research results were collected from the final project of the Master of Special Education program at the Universitas Pendidikan Indonesia (Thesis) published in the last 5 (five) years, carried out a systematic review and analyzed through an Ecological theory approach. The results obtained were: 20% of participants in the study were program implementation tests on non-single subjects and 80% used single subjects, 20% used a purely ecological approach and the remaining 80% were programs for optimizing children's growth and development. Ecological contextual frameworks are also discussed, namely Microsystems, Mesosystems, Ecosystems, Macrosystems and Chronosystems. Furthermore, ecological factors were analyzed regarding the relationship between early intervention programs and parenting programs in improving parental skills and optimizing child development. The last part also analyzes the objective conditions of parents who have children with special needs based on the results of empirical research and analyzes family understanding, family treatment, and efforts made by families before and after program implementation. So that making early intervention programs based on family resources does not only focus on children's barriers, but is more complex than that, ecological support is the most important thing in optimizing children's growth and development.